SKIN CANCER INCIDENCE IN RENAL TRANSPLANT RECIPIENTS - A SINGLE CENTER STUDY - Kalinova, Lucie; Majek, Ondrej; Stehlik, Daniel; Krejci, Karel; Bachleda, Petr (Biomedical papers, 2010)
Aims: To provide the first single-center study of a Czech renal transplant program that compares skin cancer risk estimates to the general population.Methods: We studied a total of 603 patients undergoing renal transplantation at the University Hospital Olomouc Transplant Center between January 1984 and December 2009. The mean time of follow-up was 5.5 years. Three patients were excluded for skin cancer diagnosis before transplant. The cohort was linked with the National Cancer Registry of the Czech Republic. For non-melanoma skin cancer (NMSC), the observed number of cancers were compared to the expected numbers of NMSC based on national cancer incidence rates stratified by age. The standartized incidence ratio (SIR) was calculated as observed-to-expected ratios.Results: We found a total of 127 cases of skin cancers in 55 patients. 52/55 (94.5%) were patients with non-melanoma skin cancers, 2/55 (3.6%) patients had malignant melanoma, and we uncovered one case of merkel cell carcinoma of the skin (1.8%). There were no cases of Kaposi's sarcoma, cutaneous lymphoma or malignant fibrous histiocytoma. For NMSC, the overall SIR was 7.39 (95% confidence interval 5.52-9.70). Thus, skin cancer was the most common malignant condition, representing 64.1% of all malignant tumours detected in study population.Conclusion: We confirmed that skin cancer is a major complication in renal transplant recipients. Therefore it is important to increase the intensity of surveillence for these lesions in transplant patients.
Keywords: Cancer risk/Transplantation/Skin cancer/Immunosuppression